2019
DOI: 10.1111/oik.05191
|View full text |Cite
|
Sign up to set email alerts
|

Stressor fluxes alter the relationship between beta‐diversity and regional productivity

Abstract: Dispersal of organisms can influence the relationship between beta-diversity and regional productivity in heterogeneous environments. However, many ecosystems are also linked by fluxes of stressors, with an unknown influence on this relationship. In this study, we assess the relationship between beta-diversity (measured as Bray-Curtis dissimilarity) and regional productivity (measured as biovolume) under various levels of a stressor flux in meta-ecosystems that were composed of two marine micro-algae communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The β diversity effects were not significant in 8 out of the 14 cruises (colored dash lines in Figure 2). Current research on the relationship between β diversity and metacommunity functions also find such similar pattern that β diversity generally has positive effects on ecosystem functions [73][74][75][76][77], but non-significant or even negative β diversity effects are not uncommon [8,9,78]. Interestingly, we found the variability of β diversity effects coincided with the variability of metacommunity assembly processes, as indicated by 𝛽𝑀𝑃𝑇𝐼 (Figure 3 and S3-1).…”
Section: Discussionsupporting
confidence: 77%
“…The β diversity effects were not significant in 8 out of the 14 cruises (colored dash lines in Figure 2). Current research on the relationship between β diversity and metacommunity functions also find such similar pattern that β diversity generally has positive effects on ecosystem functions [73][74][75][76][77], but non-significant or even negative β diversity effects are not uncommon [8,9,78]. Interestingly, we found the variability of β diversity effects coincided with the variability of metacommunity assembly processes, as indicated by 𝛽𝑀𝑃𝑇𝐼 (Figure 3 and S3-1).…”
Section: Discussionsupporting
confidence: 77%
“…2 ). Current research on the relationship between β diversity and the overall functions of multiple sites has also found similar patterns, showing that β diversity generally has positive effects on ecosystem functions ( 4 , 46 49 ) but that nonsignificant or even negative β diversity effects are not uncommon ( 6 , 7 , 50 ). We acknowledge that variable β diversity in the literature could stem from the difference among ecosystem types, where different levels of habitat heterogeneity, dispersal limitation, and abiotic influences will alter the relationship between biodiversity and ecosystem functioning ( 1 ).…”
Section: Discussionmentioning
confidence: 81%
“…ε = (ε 1 ,ε 2 ) T is two‐dimensional Gaussian white noise with component variances 0.01 and correlation coefficient ρ, which describes the response of population growth rate to environmental fluctuations. We calculate population variability and synchrony based on x i ( t ) to avoid the immediate influence of dispersal (de Raedt et al 2019; but see Desharnais et al 2018). Previous studies that considered both x i ( t ) and x i ′( t ) showed that these two types of models generated qualitatively similar effects of dispersal on synchrony and variability (Wang et al 2015).…”
Section: Methodsmentioning
confidence: 99%